Investigation of Subchannel Flow Pulsations Using Hybrid URANS/LES Approach - Detached Eddy Simulation - Home, Deepayan (My University, 2010)
The work presented m this thesis focused on using the hybrid Unsteady Reynolds-Averaged Navier-Stokes (URANS)/Large Eddy Simulation (LES) methodology to investigate the flow pulsation phenomenon in compound rectangular channels for isothermal flows. The specific form of the hybrid URANS/LES approach that was used is the Strelets (2001) version of the Detached Eddy Simulation (DES). It is of fundamental interest to study the problem of flow pulsations, as it is one of the most important mechanisms that directly affect the heat transfer occurring in sub-channel geometries such as those in nuclear fuel bundles. The predictions associated with the heat transfer and fluid flow in sub-channel geometry can be used to develop simplified physical models for sub-channel mixing for use in broader safety analysis codes. The primary goal of the current research work was to determine the applicability of the DES approach to predict the flow pulsations in sub-channel geometries. It was of interest to see how accurately the dynamics associated with the flow pulsations can be resolved from a spatial-temporal perspective using the specific DES model. The research work carried out for this thesis was divided into two stages.
In the first stage of the research work, effort was concentrated to primarily understand the field of sub-channel flow pulsations and its implications from both an experimental and numerical point of view. It was noted that unsteady turbulence modeling approaches have great potential in providing insights into the fundamentals of sub-channel flow pulsations. It was proposed that for this thesis work, the Shear Stress Transport (SST) based DES model be used to understand the dynamics associated with sub-channel flow pulsations. To the author's knowledge the DES-SST based turbulence model has never been used for resolving the effects of sub-channel flow pulsations. Next, the hybrid URANS/LES turbulence modeling technique was reviewed in great detail to understand the philosophy of the hybrid URANS/LES technique and its ability to resolve fundamental flows of interest. Effort was directed to understand the switching mechanism (which blends the URANS region with the LES region) in the DES-SST model for fully wall bounded turbulent flows without boundary layer separation. To the author's knowledge, the DES-SST model has never been used on a fully wall bounded turbulent flow problem without boundary layer separation. Thus, the DES-SST model was first completely validated for a fully developed turbulent channel flow problem without boundary layer separation.
In the second stage of the research work, the DES-SST model was used to study the flow pulsation phenomena on two rectangular sub-channels connected by a gap, on which extensive experiments were conducted by Meyer and Rehme (1994). It was found that the DES-SST model was successful in resolving significant portion of the flow field in the vicinity of the gap region. The span-wise velocity contours, velocity vector plots, and time traces of the velocity components showed the expected cross flow mixing between the sub-channels through the gap. The predicted turbulent kinetic energy showed two clear peaks at the edges of the gap. The dynamics of the flow pulsations were quantitatively described through temporal auto-correlations, spatial cross-correlations and power spectral functions. The numerical predictions were in general agreement with the experiments in terms of the quantitative aspects. From an instantaneous time scale point of view, the DES-SST model was able to identify different flow mixing patterns. The pulsating flow is basically an effect of the variation of the pressure field which is a response to the instability causing the fluid flow pulsations. Coherent structures were identified in the flow field to be comprised of eddies, shear zones and streams. Eddy structures with high vorticity and low pressure cores were found to exist near the vicinity of the gap edge region. A three dimensional vorticity field was identified and found to exist near the gap edge region. The instability mechanism and the probable cause behind the quasi-periodic fluid flow pulsations was identified and related to the inflectional stream-wise velocity profile. Simulations were also performed with two different channel lengths in comparison to the reference channel length. Different channel length studies showed similar statistical description of the flow field. However, frequency independent results were not obtained. In general, simulations performed using the DES-SST model were successful in capturing the effects of the fluid flow pulsations. This modeling technique has great potential to be used for actual rod bundle configurations.
Keywords: Flow Pulsations; Hybrid URANS/LES; Detached Eddy Simulation; Unsteady Reynolds-Averaged Navier-Stokes